Sources for multiple disease resistance in chickpea (Cicere arietinum) germplasm - Dua, R P; Raiger, H L; Mishra, S K; Sharma, S K; Dahiya, O P (The Indian Journal of Agricultural Sciences, 2008)
The selection of resistance sources against individual as well as multiple diseases in chickpea (Cicer arietinum L.) was carried out during 2004-05 from the germplasm available at the Gene Bank of the Bureau, New Delhi. Based on the average infection and the disease score of the germplasm accessions with respect to wilt, dry root rot, wet root rot. ascochyta blight, collar rot, botrytis gray mould and foot rot at multi-locations. the promising accessions having resistance against these diseases were selected. The number of promising accessions having resistance against individual disease were 19 for wilt, 11 for dry root rot, 24 for collar rot, 36 for wet root rot, 7 for ascochyta blight, 89 for botrytis gray mould and 481 for foot rot. For multiple disease resistance, 15 accessions (ICs 327060, 327062, 327063, 327073, 327074, 327100, 327112, 327190, 327220, 327259, 327336. 327679, 327777, 327779 and 327975) were identified as promising as these had combined resistance against wilt, dry root rot, collar rot, wet root rot and foot rot. For combined resistance against ascochyta blight and botrytis gray mould, lines IC 327414 and IC 327352 were promising.